2022
DOI: 10.1002/jsfa.12172
|View full text |Cite
|
Sign up to set email alerts
|

Flavor differences of soybean and defatted soybean fermented soy sauce and its correlation with the enzyme profiles of the kojis

Abstract: BACKGROUND Soybeans and defatted soybeans, commonly used as protein ingredients, have different flavors of their fermented soy sauce. Clarifying the differences between the two soy sauces, as well as the formation mechanism, is an important prerequisite for improving the flavor of defatted soybean soy sauce. To this goal, the aroma characteristics of two soy sauces and their volatile profiles were compared by sensory evaluation and gas chromatography‐mass spectrometry, and eight enzyme activities and volatile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…and various acid‐producing microorganisms increased, 18 ultimately causing the pH value of the soy sauce mash to decrease to 4.0 and 5.0. A low‐pH environment was more favorable for the effect of acid protease 19 . Bacillus sp.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…and various acid‐producing microorganisms increased, 18 ultimately causing the pH value of the soy sauce mash to decrease to 4.0 and 5.0. A low‐pH environment was more favorable for the effect of acid protease 19 . Bacillus sp.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the cell wall of plants was mainly composed of cellulose, hemicellulose and pectin 6 . Cellulase, xylanase, β ‐glucosidase and pectinase could degrade the cell wall of raw materials during fermentation and release intracellular nutrients into the fermentation system for microbial growth and multistage transformation of substances 4,6,19 . During the first 30 days of fermentation, the activity of cellulase was more stable than that of xylanase, β ‐glucosidase and pectinase, probably due to the excellent salt and acid resistance of cellulase and the proliferation of microorganisms capable of producing highly active cellulase, such as Bacillus sp 20,22,23 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the highest acetic acid content was found in sample T0, accounting for 19.3 g/100 mL at day 30, followed by T0W5, accounting for 19.1 g/100 mL. Previous studies showed that the production of lactic acid could improve the taste of fermented soy sauce by neutralising the saltiness of soy sauce, making the flavour more refreshing, whereas the formation of acetic acid, as a volatile fatty acid, contributes to the sour smell of soy sauce [ 5 , 39 , 40 , 41 ]. The inoculation of W. anomalus accelerated the production of lactic acid, which could be beneficial to flavour formation in moromi fermentation.…”
Section: Resultsmentioning
confidence: 99%